Diseño de un modelo de gestión por procesos para el departamento de producción gráfica de Graffito Ideas Impresas Cía. Ltda. - Torres de la Torre, Carlos Robert (2014)
This study aimed to design a process management model for the company called Graffito Ideas Impresas, which contributes to improve the value adding processes in the provision of printing services. It was applied a diagnosis based on data provided by the company management setting a process map focused on adding value elements (prepress, press and finishes) defining subprocess that allowed the development of methods since the start until the activity ends, a procedures manual was developed to guide the operation to be performed. This process management model seekscontrol and operational improvement indicators for which each thread is made to measure efficiency and effectiveness